2013
DOI: 10.1007/s00253-013-5339-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cellodextrin transporters from Neurospora crassa in Saccharomyces cerevisiae for cellobiose fermentation

Abstract: Saccharomyces cerevisiae can be engineered to ferment cellodextrins produced by cellulases as a product of cellulose hydrolysis. Direct fermentation of cellodextrins instead of glucose is advantageous because glucose inhibits cellulase activity and represses the fermentation of non-glucose sugars present in cellulosic hydrolyzates. To facilitate cellodextrin utilization by S. cerevisiae, a fungal cellodextrin-utilizing pathway from Neurospora crassa consisting of a cellodextrin transporter and a cellodextrin h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…Despite the promising results from the cellobiose fermentation experiments, transient cellodextrin accumulation by the transglycosylation of ␤-glucosidase was observed in the medium during the processes (24). The accumulated cellodextrin might decrease the ethanol productivity because the cellodextrin transport and reconsumption might not be as rapid as the cellobiose fermentation (22,24). S. cerevisiae strain D452-2 expressing the cellodextrin transporter and ␤-glucosidase from episomal plasmids (DCDT-1G) accumulated 15.5 g/liter of cellodextrin in the fermentation experiments using YP medium with 80 g/liter cellobiose under oxygen-limited conditions.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Despite the promising results from the cellobiose fermentation experiments, transient cellodextrin accumulation by the transglycosylation of ␤-glucosidase was observed in the medium during the processes (24). The accumulated cellodextrin might decrease the ethanol productivity because the cellodextrin transport and reconsumption might not be as rapid as the cellobiose fermentation (22,24). S. cerevisiae strain D452-2 expressing the cellodextrin transporter and ␤-glucosidase from episomal plasmids (DCDT-1G) accumulated 15.5 g/liter of cellodextrin in the fermentation experiments using YP medium with 80 g/liter cellobiose under oxygen-limited conditions.…”
Section: Discussionmentioning
confidence: 96%
“…These results indicated that not only the absolute increase of the copy numbers of cdt-1 and gh1-1 but also their ratio is important for the large improvement in cellobiose fermentation that we observed in the evolved strain EJ2. Despite the promising results from the cellobiose fermentation experiments, transient cellodextrin accumulation by the transglycosylation of ␤-glucosidase was observed in the medium during the processes (24). The accumulated cellodextrin might decrease the ethanol productivity because the cellodextrin transport and reconsumption might not be as rapid as the cellobiose fermentation (22,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellobiose Uptake, but Still Allow Cellulase Gene InductionWhen heterologously expressed in S. cerevisiae, CDT-1 and CDT-2 have been shown to be high-affinity transporters, with CDT-1 acting as a proton symporter and CDT-2 acting as a facilitator (33). To identify functionally important residues within the cellodextrin transporters, CDT-1 and CDT-2, several conserved amino acids were individually mutated to alanine.…”
Section: Point Mutants In Cdt-1 and Cdt-2 Significantly Decreasementioning
confidence: 99%
“…S1A in the supplemental material) (5). We hypothesized that cellobiose consumption results in an ATP deficit in glycolysis relative to glucose, due to the fact that the cellodextrin transporter (CDT-1) in the cellobiose-utilizing pathway is a proton symporter, requiring ATP hydrolysis for cellobiose uptake (7). Moreover, under anaerobic conditions, ATP production is limited to substrate-level phosphorylation, further restricting ATP availability.…”
Section: Resultsmentioning
confidence: 99%